PERSEPSI PASIEN TENTANG MUTU PELAYANAN ADMISI, KEPUASAN PASIEN DAN KETEPATAN ADMISI DI RUMAH SAKIT SEMEN GRESIK (PATIENT PERSEPTION OF ADMISSION SERVICE QUALITY, PATIENT SATISFACTION WITH APPROPRIATENESS ADMISSION AT THE - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Background: The Semen Gresik Hospital is a type C private hospital with 100 beds and belongs to PT Semen Gresik. The Bed Occupancy Ratio since 1997 to 1999, was 48%, 50,4% and 59.5%. This study was to know patients' perception on admisÂ¬sion service quality